Mediocre and harmful public sector leadership. Issue 4 (31st October 2019) - Franken, Esme; Plimmer, Geoff
Abstract : Purpose: Leadership matters in public contexts. It influences employee development and, in turn, the effective delivery of public services. Harmful leadership limits the fulfilment of both these requirements. Although there are many studies of public leadership, few explore aspects of poor leadership focusing on leading people, in the unique public sector context. The purpose of this paper is to explore the public sector environment as one that can enable harmful leadership, and identifies what those aspects of harmful behaviours are. In particular, it focuses on common, day-to-day forms of harmful mediocre leadership rather than more dramatic, but rarer, forms of destructive or toxic leadership. Design/methodology/approach: The study was conducted over three phases. In study one ( N =10) interviews using the critical incident technique identified harmful behaviours. Study two ( N =10) identified perceived causal processes and outcomes of these processes. Study three was a validation check using two focus groups ( n =7) and two further interviews ( n =6). Findings: Four dimensions of harmful behaviour were found: micromanagement, managing up but not down, low social and career support and reactive leadership. Several pathways to harm were found, including lessened employee confidence, motivation, collaboration, learning and development. Research limitations/implications: This research is limited by a small sample and data collected in one public sector system. But its implications are still meaningful. The research identified some ways that harmful leadership can occur, that is missed in existing studies of harmful leadership, which tend to focus on more toxic forms of harm. The role of NPM and other reforms as important shapers of current leadership behaviours are also discussed. Practical implications: To address these behaviours further investment in leadership development, selection and performance management is recommended. Social implications: Social implications include the hindering of effective service delivery and limited ability to deal with increasingly dynamic and complicated problem. Originality/value: Public sector leadership studies are often rose tinted, or describe what should be. Instead, this paper describes what sometimes is, in terms of day-to-day mediocre but harmful leadership.